A Critique on the Legal Framework for Combating Human Trafficking in Nigeria - Dyitkuka, Joanna Rotdelmwa; Musa-Agboneni, Omomen (ABUAD Law Journal, 2023)
Human trafficking is a menace that affects the global community, because of its adverse effect on the members of the society. It is therefore a violation of the human rights of persons and is believed to oppress thousands of people globally. In Nigeria, there is a legal framework to combat human trafficking, however, human trafficking still remains a major concern that has eaten so deep into the fabric of Nigeria and has become very complex to tackle. Human trafficking just like any other crime has evolved and is still evolving as society evolves. Therefore, there is an expectation that laws are constantly in conformity with the current trends and practices of human trafficking in a community. This study aims to critically critiquethe position of the law on human trafficking in Nigeria, the gaps present in these laws and make recommendations to effectively fight against human trafficking. This study also recommends that further amendments of the extant laws should comply with the present-day realities.